The Effect of Sugar Concentration on The Organoleptic Quality of Nata De Coco-Leri - Ghina Amirah Mulyani; Iswadi Iswadi; Samingan Samingan; Wiwit Artika; Yaumil Istiqlal M.Nur (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
ABSTRACTOrganoleptic or sensory test or sensory test is a test method in which the human senses function as the main instrument to determine whether a product is accepted. Organoleptic quality testing plays an essential role in implementing quality control. This study aimed to determine the effect of granulated sugar concentration on the organoleptic quality of nata de coco-leri. This study applied the experimental method with a non-factorial, Completely Randomized Design (CRD), including five treatments (negative control, 1%, 1.5%, 2%, and 2.5% granulated sugar) with four replications. The parameters observed in this study were the organoleptic quality of nata de coco-leri. The data were analyzed quantitatively using Analysis of Variance (ANOVA) and the BNJ Follow-Up Test at a significant level of α = 0.05. The results of the analysis of variance (ANOVA) and BNJ tests explained that there was an effect of significantly different concentrations of granulated sugar on organoleptic quality, including elasticity, color, taste, texture, and aroma of nata de coco-leri. This study concludes that the concentration of 2.5% granulated sugar is the nata product that has the most significant effect on the organoleptic quality of nata de coco-leri.Keywords: Nata, granulated sugar, organoleptic ABSTRAKOrganoleptik ataupun uji indra ataupun uji sensori yakni suatu metode pengujian dimana indra manusia sendiri berfungsi sebagai instrumen utama untuk menentukan diterima ataupun tidaknya suatu produk. Pengujian kualitas organoleptik memainkan peran penting dalam penerapan kontrol kualitas. Tujuan penelitian ini guna mengetahui pengaruh konsentrasi gula pasir terhadap mutu organoleptik nata de coco-leri. Penelitian ini menerapkan metode eksperimen dengan Rancangan Acak Lengkap (RAL) non faktorial mencakup 5 perlakuan (kontrol negatif, perlakuan 1%, 1,5%, 2% dan 2,5% gula pasir) dengan 4 ulangan. Parameter yang dilakukan pengamatan pada penelitian ini yakni mutu organoleptik dari nata de coco-leri. Data dilaksanakan analisis secara kuantitatif dengan Analisis Varian (ANAVA) serta Uji Lanjut BNJ pada taraf signifikan α = 0,05. Hasil uji analisis varian (ANAVA) dan BNJ menerangkan bahwasanya terdapat pengaruh konsentrasi gula pasir yang berbeda nyata terhadap mutu organoleptik meliputi kekenyalan, warna, rasa, tekstur serta aroma nata de coco-leri. Kesimpulan dari penelitian ini yakni konsentrasi 2,5% gula pasir yakni produk nata yang paling berpengaruh nyata terhadap mutu organoleptik nata de coco-leri.Kata Kunci: Nata, gula pasir, organoleptik